EFFECT OF EXERCISE SKIP FOR HEIGHT TO POWER LEG MUSCLE IN THE MEN’S VOLLEYBALL TEAM PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI PEKANBARU - Nurbaeti '; Saripin '; Ni Putu Nita Wijayanti Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT : The issues raised in this study is